(untitled) (Plant Tissue Culture and Biotechnology, 2024)
The limitation of planting material is the major drawback to expanding pear cultivation in Sri Lanka. Hence, an in vitro protocol was developed to produce planting material for the pear variety of Rahangala. Pear shoots were used as explants and surface sterilization of explants was done using 0.5% and 1% (w/v) AgNO3 for 15 min, 5% and 10% (v/v) NaOCl for 5, 10 and 15 min. In vitro shoot multiplication and root induction were found to be suitable in full and half strengths of MS medium respectively supplemented with various concentrations of BAP (1, 1.5, 2, 2.5, 3 mg/l), IBA (0, 0.5, 1, 2, 3, 4 mg/l) and NAA (0.1 mg/l). Acclimatization was conducted in pots containing different proportions of topsoil, compost, coir dust and sand. Completely Randomized Design (CRD) was used as an experimental design for this study. During sterilization of explants, the survival rate of 86.6% was recorded after 3 weeks where the treatment was done with 1% AgNO3, and 10% NaOCl for 10 min. BAP (3.0 mg/l) produced the best shoot multiplication (1.46 ± 0.2). Significantly (p<0.05), the highest mean number of roots (1.93 ± 0.98), average length (60.6 mm), and rooting percentage (68%) were observed in ½ MS medium with 4.0 mg/l IBA. After five weeks of transplantation in pots, 100% of plantlets survived in topsoil, compost, coir dust, and sand in a ratio of 1:1:1:1 Plant Tissue Cult. & Biotech. 34(1): 25-33, 2024 (June)